EFEKTIVITAS DAN DAMPAK KEBIJAKAN TAX AMNESTY BAGI PEREKONOMIAN INDONESIA - Lusy Lusy; Richard Andrew; Josephine Rebeka Teresa (ITB AAS INDONESIA, 2023)
Taxes have a very important role for a country, the main income of Indonesian state itself also comes from taxes. At the end of August 2021, taxes had donate 1.74% of all state revenues, however, tax revenues were still not optimal. To push state tax revenues, the government proposes a tax amnesty policy (Tax Amnesty). Tax Amnesty is the abolition of taxes that should be paid by disclosing assets and paying a ransom as regulated in Law no. 11 of 2016 concerning Tax Amnesty. The General Purpose of Tax Amnesty is carried out to withdraw